2021
DOI: 10.1038/s41598-021-89926-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoke from regional wildfires alters lake ecology

Abstract: Wildfire smoke often covers areas larger than the burned area, yet the impacts of smoke on nearby aquatic ecosystems are understudied. In the summer of 2018, wildfire smoke covered Castle Lake (California, USA) for 55 days. We quantified the influence of smoke on the lake by comparing the physics, chemistry, productivity, and animal ecology in the prior four years (2014–2017) to the smoke year (2018). Smoke reduced incident ultraviolet-B (UV-B) radiation by 31% and photosynthetically active radiation (PAR) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 56 publications
0
55
0
Order By: Relevance
“…Increased abundance of aerosols resulting from wildfire smoke and the dust and plant volatile compounds released during droughts can decrease the amount of UV radiation and change the spectral composition of sunlight received by organisms at ground level [ 109 ]. Notably, changes in air quality resulting from fires and droughts can occur well beyond the location of these events [ 32 , 110 , 111 ].…”
Section: Interactive Effects Of Uv Radiation and Extreme Climate Even...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased abundance of aerosols resulting from wildfire smoke and the dust and plant volatile compounds released during droughts can decrease the amount of UV radiation and change the spectral composition of sunlight received by organisms at ground level [ 109 ]. Notably, changes in air quality resulting from fires and droughts can occur well beyond the location of these events [ 32 , 110 , 111 ].…”
Section: Interactive Effects Of Uv Radiation and Extreme Climate Even...mentioning
confidence: 99%
“…For example, the plants that colonise open habitats and tolerate high UV radiation may include more introduced and fewer specialised or endemic species [107,108] which may, in turn, have negative consequences for biodiversity. Increased abundance of aerosols resulting from wildfire smoke and the dust and plant volatile compounds released during droughts can decrease the amount of UV radiation and change the spectral composition of sunlight received by organisms at ground level [109]. Notably, changes in air quality resulting from fires and droughts can occur well beyond the location of these events [32,110,111].…”
Section: The Impacts Of Eces On Terrestrial Ecosystems Can Occur Over...mentioning
confidence: 99%
“…However, we recognize that our study only covered the epilimnetic zone of the lake, and that PAR reduction could have lessened productivity at greater depths or caused a shift in the depth of the euphotic zone. Scordo et al (2021) found that after smoke reduced PAR at depth (12.5 m and lower) in Castle Lake, the deep chlorophyll-a and productivity maximum (15-20 m) did not develop. Giling et al (2017) showed that metalimnetic contribution to whole-lake metabolism can be highly variable.…”
Section: Discussionmentioning
confidence: 90%
“…Also, the year 2018 had the highest mean (51 ± 5 μg m −3 ) and maximum (143 μg m −3 ) value of PM 2.5 when smoke was present (Figure 3a). During 2018, our study period began on August 1st, 13 days after the smoke conditions started (Scordo et al., 2021). Within our study period, smoke cover occurred between August 1–19, August 21–25, August 29–30, and September 5–10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation